(untitled) (Journal of actual problems of jurisprudence, 2019)
This article is the result of a comprehensive study conducted by the authors. In this article the authors examine the issues of criminal law measures to combat crimes committed by migrants. This issue is of particular relevance in connection with the tendency of increase the number of crimes committed by migrants. These facts necessitate the study of issues of criminality of migrants and measures to counter them. Key words: crime, migrant, criminal law measures, struggle, resistance.